A novel research platform for sudden cardiac death based on continuous, real-life, unlimited follow-up of a cohort of high-risk patients. (14th October 2021) - Boveda, S.B; ,
Abstract: Background/Introduction: Currently, Sudden Cardiac Death (SCD) prevention is mainly based on implantable cardioverter-defibrillator (ICD) implantation in high risk patients. Real-time, prospective follow-up of such high-risk patients can afford a unique opportunity to improve SCD prevention. We previously conducted an exploratory retrospective project (DAIPP pilot program) focusing on >5 000 ICD recipients, which provided us with valuable information and knowledge to set up a wider, prospective project (1–11). Purpose: We present here the organizational outline for an innovative research platform for SCD, based on a real-life cohort with continuous, unlimited follow-up. The overall aim is to garner high-value information which can help optimize individualized risk stratification, cardiac defibrillation, and preventive strategies to eventually decrease SCD burden. Methods and results: The DAIPP Consortium is an investigator-initiated, prospective, multicentre, independent, long-term, academic cohort study, focusing on patients at high risk of SCD and implanted with an ICD. More than 5 000 ICD recipients will be enrolled prospectively and consecutively through 17 French tertiary public and private hospitals during the first three years. All patients will be monitored continuously through a unique remote monitoring platform, and they will be linked to the national "Health Data Hub", gathering information about medications, hospitalizations and outcomes. Quality and exhaustivity of the collected data will be regularly monitored through systematic monthly automatic indices in each center. Events will be centrally adjudicated. For the 2021–2023 period, 6 work-packages have already been created within the research platform, some being clinical and others translational research, including ischemic cardiomyopathy, new technologies, congenital cardiomyopathies, channelopathies, complications and artificial intelligence, to develop new approaches. Concomitantly, the consortium will be open to external collaborations, and an academic research program has been initiated with various European universities to enable Master, PhD and Post-doctoral students to conduct their research on SCD. Conclusion: DAIPP is an investigator-initiated real-life continuous follow-up cohort of patients at high risk of SCD. This project will provide an open research platform to enhance the understanding of, and improve preventive strategies for SCD. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Inserm, Société Française de Cardiologie, Clinique Pasteur